MACROAGGREGATION OF A PALEUDALF AFFECTED BY CAVITATION INTENSITY AND MANAGEMENT SYSTEMS WITH COVER PLANTS - Silva, Érika Andressa; Mallmann, Micael Stolben; Pereira, Monike Andrade; Pons, Sarah Severo; Bertol, Felipe Dalla –Zen; Reinert, Dalvan José; Reichert, José Miguel (Revista Brasileira de Engenharia de Biossistemas, 2021)
Ultrasonic-based techniques allow the prediction of the energy required to break the aggregate and have been more commonly used to measure the stability of aggregates. Although they result in the same applied energy, certain combinations of time and power might correspond to different intensities of cavitation. Consequently, different responses in aggregation indexes can be obtained with different configurations of ultrasound techniques. Thus, this work was carried out to evaluate the effects of cavitation intensity in the distribution of aggregates of a Paleudalf under management systems with cover plants and to compare aggregate stability determination methods (ultrasound versus wet sieving). Aggregate samples of the BS (bare soil), OT (black oat + forage turnips) and OV (black oat + hairy vetch) treatments were exposed to ultrasonic irradiation in different combinations of potency and time: (U1) 74.5 W/4 s; (U2) 49.7 W/6 s; (U3) 74.5 W/10 s and (U4) 49.7 W/15 s. After each sonification, the samples were passed in the same set of sieves used in the standard method of wet sieving -WS (8.00 - 4.76, 4.76 - 2.00, 2.00 - 1.00, 1.00 - 0.25 and < 0.25 mm) and the geometric mean diameter (GMD) and mass-weighted mean diameter (WMD) were calculated. The amplitude of vibration exerted a greater influence on soil breakdown than the total energy applied. Compared to the ultrasound method, in the WS method observed higher percentage of retained aggregates in the size class 8-4.76 mm and, consequently, greater aggregation indexes GMD and WMD.